Trapelus boehmei (Wagner, Melville, Wilms & Schmitz, 2011) (Squamata: Agamidae): New locality record in the South-west of Algeria at Tindouf - Mayssara, El Bouhissi; Fayçal, Seddiki; Abdelwahab, CHEDAD (جامعة الوادي - University of Eloued, 2022)
Trapelus boehmei (Squamata: Agamidae) is distributed on the High Plateau of North Algeria, from M’sila to Naâma and Tlemcen-south. An uncertain presence noted from El Tarf to Batna and Tebessa in Northeast of Algeria. In this note, a new locality of this species at Tindouf region of Southwest of Algeria.
article
Keywords: Reptilia, Trapelus boehmei, Tindouf, South-west Algeria.